Explainable AI-Driven TabNet Model Enhanced with Bayesian Optimization for Lung Cancer Prediction and Interpretation - Ilham Maulana (Kresnamedia Publisher, 2024)
This study aims to develop an accurate and explainable lung cancer risk prediction model using a TabNet approach optimized with Bayesian Optimization and applying Explainable AI (XAI) methods through LIME (Local Interpretable Model-Agnostic Explanations). TabNet was selected for its efficiency in processing tabular data and its ability to produce high-accuracy predictions. In the initial stage, the TabNet model was tested using a dataset that was preprocessed through standardization and split into training and testing sets. The performance evaluation of the model without optimization showed an accuracy of 95.83%, precision of 95.87%, recall of 95.76%, and F1-Score of 95.81%. Subsequently, Bayesian Optimization was applied using the Optuna library to find the best hyperparameter combination for the TabNet model. The optimization results demonstrated a significant improvement, achieving an accuracy of 98.33%, precision of 98.48%, recall of 98.21%, and F1-Score of 98.32%. After optimizing the TabNet model, LIME was implemented to provide interpretability for the generated predictions. LIME was used to identify the most influential features contributing to the predictions, enhancing the model's transparency in the lung cancer risk prediction process. Through the combination of TabNet, Bayesian Optimization, and Explainable AI, this study successfully developed a lung cancer prediction model that is not only accurate but also highly interpretable. This model can assist medical professionals in identifying key risk factors and providing transparent explanations for each prediction made.